The relevance of increasing the role of building materials in green construction - Serdyuk, V.; Rudchenko, D. (Ways to Improve Construction Efficiency, 2019)
The article shows the relevance of the implementation of "green" standards aimed at reducing energy consumption and improving the environment. The trends of temperature rise due to carbohydrate combustion emissions are shown, comparative parameters of conventional and green construction are given. It is argued that "green" construction should cover all stages of building and existence of a building: design, construction, operation, dismantling, recycling. A high level of comfort and safety, a low energy and resource consumption must be ensured at the construction stage, and at the final stage of the building operation all building materials must be recycled and reused. At the same time, an extremely important function is fulfilled by the regulatory framework in the construction industry, which has been updated with great delay (regulatory requirements) in Ukraine, compared with European countries. The review of the main wall materials from the point of view of energy intensity of their production is given. The organizational and technological possibilities of increasing the role of autoclave aerated concrete in construction and the prospects of transition of low density aerated concrete production are revealed. An important role is played by the increase in the production of autoclave aerated concrete as a structural and thermal insulation and thermal insulation material, which contributes to the rational use of energy resources in construction indirectly leading to a reduction of greenhouse gas emissions. The priority directions for improving the production of autoclaved aerated concrete are given, namely: reducing the density of aerated concrete from D600 to D400 and to D300 provides a multifunctional effect, which consists of increasing the thermal resistance of a single-layer aerated concrete wall to the regulatory requirements (R ≥3,3 м2‧° С/Vt ), reducing the weight of the wall structure and load on the foundations, reducing material consumption and reducing by 22-30% the cost of cement and lime. Moving production to low density simultaneously solves several important issues related to energy and material savings, reduced greenhouse gas emissions and the cost of the building itself.